(untitled) (Colombia Medica, 2012)
Introduction: The host niche for Staphylococcus aureus (SA) are the anterior nares; however, vaginal colonization rates between 14% and 17.1% in pregnant women have been recently reported, raising interest about the potential risk in postpartum women and in neonates from colonized mothers. Objectives: To determine the prevalence of nasal and vaginal colonization of SA and the antibiotic susceptibility of the isolates in pregnant women attending a maternity hospital in Cartagena, Colombia. Methods: Nasal and vaginal swabs were obtained from participants and subjected to microbiological and molecular assays. A post discharge follow-up was performed for up to four weeks. Results: From 100 pregnant women enrolled in the study, 34 were colonized with SA; 29 only in the nares, three only in the vagina, and two at both sites. Colonization of pregnant women with SA was more common in the nares than in the vagina or at both sites [29/34 (85.3%) vs 3/34 (8.8%) and 2/34 (5.9%); p<0.05]. We obtained 36 SA isolates, nine (25%) of which were methicillin-resistant Staphylococcus aureus (MRSA), one was from the vagina; thus, the overall MRSA colonization rate among pregnant women was 9%. Molecular analysis showed that Panton-Valentine leukocidin (PVL) genes were carried by the vaginal MRSA, seven of the nasal MRSA, and two of the Methicillinsensitive Staphylococcus aureus (MSSA) isolates. Two MRSA isolates carried SCCmec type I and seven carried SCCmec type IV. Conclusions: Nasal colonization rate for SA in the study population was similar to previous reports. However, the frequency of nasal colonization of MRSA was higher while vaginal colonization of SA was lower than previously reported in other studies for similar populations. The MRSA isolates obtained showed a community profile.